(untitled) (American Journal of Islam and Society, 2019)
New scholarship, covered by the books in this review essay, include studies of mosques in the UK, Canada, Spain and Australia and demonstrate that the proclamation of presence of the architecture of the mosque works on a number of levels. The exterior façade, of course, functions to symbolize some sort of landmark and identity in a variety of possible architectural languages. However, the interior, is where the differences truly lie between the mosque in constructed in the Muslim world and those constructed outside of the Muslim world. For minority communities, the mosque program necessarily includes facilities for education, recreation, festive gathering and dining in addition to other specific programs such as funeral preparation, food bank collection and so forth. The contemporary mosque in the non-Muslim world, regardless of how west, north or south it is located, is loaded with much more programmatic demand in addition to the perceived politics of creating presence and identity in a perceived foreign landscape. To download full review, click on PDF.